Estudo do remodelamento da lâmina própria da laringe relacionado ao processo de senilidade - Branco, Anete Antunes de Oliveira [UNESP] (2014)
Objective: to study the remodeling of collagen types I, III, IV and V, elastin, fibronectin, laminin and hyaluronic acid using immunohistochemical techniques during the aging process of human larynx. Casuistic and Methods: thirty male human vocal folds were removed during routine autopsy in the Department of Pathology at Botucatu Medical School/UNESP, of these, twenty elderly men (n-10; 60-75 years and n-10, over 75 years) and 10 adult male (30-50 years). The fragments of vocal folds received the immunohistochemical techniques for collagens types I, III, IV and V, elastin, fibronectin, laminin and hyaluronic acid. The readings of the lamina propria were carried out taking into account the accumulation of brownish color of its structures as well as basal membrane, given the standard area in μm2 and the result in percentage of area by the ImageJ software. Results: there was an increase of immunoexpression of collagen types I and III in the larynxes of the elderly (p≤0.05). The values registered in the collagen type I on the superficial layer of the three age groups were respectively, 34.2%, 39.6% and 40.4%, whereas 31.8%, 44.4% and 46.9% in the deep layer. The values of the collagen type III in the superficial layer of the three age groups were respectively, 25.6%, 31.2% and 32.4%; while in the deep layer the values were 23.6%, 24.6% and 29.9%. For the collagen types IV and V, a higher intensity in the immunoexpression of these antibodies in the vascular endothelium of the superficial layer as well as the basal membrane was observed. The registered values for collagen type IV in the superficial layer in the three age groups were respectively 20.9%, 20.7% and 21.3% as well as 17.6%, 19.3% and 20.4% in the deep layer. The values of collagen type V in the superficial layer in the three age groups were respectively 38.5%, 36.2% and 31.8%; and in the deep layer, 36.6%, 35% and 31.3%. There was an increase of immunoexpression of fibronectin ...